2015
DOI: 10.1101/lm.037820.114
|View full text |Cite
|
Sign up to set email alerts
|

The sodium-activated potassium channel Slack is required for optimal cognitive flexibility in mice

Abstract: Kcnt1 encoded sodium-activated potassium channels (Slack channels) are highly expressed throughout the brain where they modulate the firing patterns and general excitability of many types of neurons. Increasing evidence suggests that Slack channels may be important for higher brain functions such as cognition and normal intellectual development. In particular, recent findings have shown that human Slack mutations produce very severe intellectual disability and that Slack channels interact directly with the Fra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

9
43
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
1
1

Relationship

2
6

Authors

Journals

citations
Cited by 31 publications
(54 citation statements)
references
References 90 publications
9
43
1
Order By: Relevance
“…This suggests that perturbation of normal KCNT1 protein function, rather than the loss of its function, underlies the pathogenic mechanism that leads to the observed phenotypes. This may be consistent with the phenotypes observed in a Kcnt1 null mouse model,70 which shows slightly reduced locomotive activity and impaired reverse learning memory and adaptation to new environments, but no seizures. Animal models based on KCNT1 mutations observed in human patients will be required in order to accurately analyse the mechanism of these disease-causing mutations.…”
Section: Effects Of Kcnt1 Mutations On Channel Functionsupporting
confidence: 88%
See 1 more Smart Citation
“…This suggests that perturbation of normal KCNT1 protein function, rather than the loss of its function, underlies the pathogenic mechanism that leads to the observed phenotypes. This may be consistent with the phenotypes observed in a Kcnt1 null mouse model,70 which shows slightly reduced locomotive activity and impaired reverse learning memory and adaptation to new environments, but no seizures. Animal models based on KCNT1 mutations observed in human patients will be required in order to accurately analyse the mechanism of these disease-causing mutations.…”
Section: Effects Of Kcnt1 Mutations On Channel Functionsupporting
confidence: 88%
“…Two of the rodent transcripts are termed Slack-A and Slack-B. Studies in mouse and rat showed that these transcripts have differing expression patterns in the brain and produce proteins with different electrophysiological properties 4 52 70 71. Slack-A is rapidly activated following depolarisation while Slack-B has slower activation kinetics 4.…”
Section: Structure Expression and Function Of Kcnt1 And Its Protein mentioning
confidence: 99%
“…After removing excessive dye with ethanol 80% (v/v), tumour sections were dehydrated again with 100% ethanol (v/v) and toluol and finally embedded in DePeX (VWR, Darmstadt, Germany). To identify SK4 channels in tumour biopsies, we adopted an established immunohistochemical method (Bausch et al ., 2015). In brief, sections were encircled with ImmEdge Hydrophobic Barrier Pen (Vector Laboratories, Burlingame, CA) and then fixed again for 15 min in 4% paraformaldehyde/PBS solution.…”
Section: Methodsmentioning
confidence: 99%
“…A state of prolonged activation among sodium channels can induce significant changes in neuronal excitability and function [41]. Alternatively, potassium channels that are activated by an increase in cytoplasmic levels of sodium ions [42] (known as K Na channels) may contribute to learning deficits that we identified in our sample [43]. Importantly, this literature suggests that our negative 3PBA metabolite finding on mental development may be a consequence of exposure to a type II pyrethroid, whereas the positive DCCA-t metabolite finding may reflect exposure to a type I pyrethroid.…”
Section: Resultsmentioning
confidence: 99%